فعالية الرقابة الجبائية في الحد من ظاهرة الغش والتهرب الضريبي - صيد بلقاسم (My University, 2024)
This memorandum addresses the issue of tax control and its role in reducing tax evasion, as we touched on tax control as it is considered an important tool within the declarative tax system, with its management and effectiveness that is built on the validity and credibility of the information provided by the taxpayer ،As the tax oversight works to discover all violations and abuses committed with the aim of pushing taxpayers to declare complete and correct information about the incomes they achieve, on the other hand, an analysis of the phenomenon of tax evasion, its causes, and the various methods used in order to get rid of tax payment, as well as the effects resulting from this phenomenon, was discussed. The aim of the study is to discover the effectiveness of fiscal control in reducing tax evasion, and it has been tested This is according to an applied study through tax investigations represented by the investigation into the taxpayer’s accountability.، Keywords:
Keywords: Fiscal control - tax evasion - tax fraud